A Complete Two-Dimensional Avalanche Photodiode Based on MoTe2−WS2−MoTe2 Heterojunctions With Ultralow Dark Current - Ouyang, Tenghui; Wang, Ximiao; Liu, Shaojing; Chen, Huanjun; Deng, Shaozhi (Frontiers in Materials, 2021)
Two-dimensional (2D)-material-based photodetectors have recently received great attention due to their potentials in developing ultrathin and highly compact devices. Avalanche photodetectors (APDs) are widely used in a variety of fields such as optical communications and bioimaging due to their fast responses and high sensitivities. However, conventional APDs based on bulk materials are limited by their relatively high dark current. One solution to tackle this issue is by employing nanomaterials and nanostructures as the active layers for APDs. In this study, we proposed and fabricated an atomically-thick APD based on heterojunctions formed by 2D transition metal dichalcogenides (TMDs). A typical device structure was formed by stacking a semiconducting monolayer WS2 onto two metallic few-layer MoTe2 flakes. Due to the Schottky barrier formed between the TMD layers and their atomic thicknesses, the dark current of the APD is greatly reduced down to 93 pA. In addition, the APD can operate through a broad spectral range from visible to near-infrared region, with a responsivity of 6.02 A/W, an external quantum eﬃciency of 1405.86%, and an avalanche gain of 587. We believe that the 2D APD demonstrated here provides a feasible approach for developing all-2D optoelectronic devices with simultaneous high-sensitivity and low noise.